Putting the hadron beam scenario for extreme blazars to the test with the Cherenkov Telescope Array. Issue 2 (27th October 2018) - Tavecchio, F; Romano, P; Landoni, M; Vercellone, S
ABSTRACT: Hadron beams are invoked to explain the peculiar properties of a subclass of BL Lac objects, the so-called extreme BL Lacs (EHBLs). This scenario predicts a quite distinctive feature for the high-energy gamma-ray spectrum of these sources, namely a hard energy tail extending up to ∼100 TeV. It has been proposed that the detection of this tail can offer an unambiguous way to distinguish between the hadron beam scenario and the standard one, which instead assumes gamma-ray emission from the jet strongly depleted at the highest energies ( E > 30 TeV) because of the interaction with the optical-IR cosmic radiation field. We present dedicated simulations of observations through the presently under construction Cherenkov Telescope Array (CTA) of the very high energy spectrum of the prototypical EHBL 1ES 0229+200 assuming the two alternative models. We demonstrate that, considering 50 h of observations from the southern site of CTA (the most sensitive at the highest energies), in the case of the hadron beam model it is possible to detect the source up to 100 TeV. This, together with the non-detection of the source above 10 TeV in the standard case, ensures that CTA observations can be effectively used to unambiguously confirm or rule out the hadron beam scenario.